Epidemiology of Acromioclavicular Joint Injuries in Professional Baseball. Issue 7 (31st July 2020) - Ramkumar, Prem; Frangiamore, Salvatore; Jones, Grant; Soloff, Lonnie; Pollack, Keshia; Curriero, Frank; Schickendantz, Mark; Frantz, Travis
Objectives: Shoulder injuries account for a large portion of all recorded injures in professional baseball. Much is known about other shoulder pathologies in the overhead athlete, but the incidence and impact of acromioclavicular (AC) joint injuries in this population is unknown. The purpose of this study was to examine the incidence, rates, and characteristics of AC joint injuries in professional baseball, and determine the impact on time missed. Methods: The Major League Baseball Health and Injury Tracking System (HITS) was used to compile records of all major and minor league player from 2011-2017 with documented AC joint injuries. These injuries were classified as acute (sprain or separation) or chronic (AC joint arthritis or distal clavicular osteolysis), and associated data included laterality, date of injury, player position, activity, mechanism of injury, length of return to play (RTP), and need for surgical intervention. Results: A total of 312 AC joint injuries (183 MiLB, 129 MLB; range 39-60 per year) were recorded (acute n=201, 64.4%; chronic n=111, 35.6%). A total of 81% of acute injuries resulted in time missed with an average RTP of 22.8 days whereas 59% of chronic injuries resulted in days missed with an average RTP of 32.2 days (p<0.001). Acute injuries occurred most commonly in outfielders (42.7%), followed by infielders (27.3%). Chronic injuries were seen in higher proportions among pitchers and catchers (45.5-56.4% chronic injuries). Acute AC injuries occurred most often while playing defense (n=100; 49.8%) in the infield or outfield (n=138; 68.7%), with 63.2% the result of a contact injury. Chronic AC joint injuries were most commonly with throwing or pitching (n=48; 43.2%) and non-contact injuries (n=79; 71.2%). Conclusion: Acute AC joint injuries are contact injuries occurring most commonly among infielders and outfielders that result in more than 3 weeks missed before return to play whereas chronic AC joint injuries occur more commonly in pitchers and catchers from repetitive overhead activity. Knowledge of these data can better guide expectation management in this elite population to better elucidate the prevalence of two common injury patterns in the acromioclavicular joint.